Study on the Effects of Protective Layer on the Electron and Hole Transmission of Cadmium Sulfide (CdS) Photocatalyst Based on a Simple Quantum Mechanical Model - Selly Alawiyah; Azrul Azwar; Fatimah Arofiati Noor (FMIPA, Universitas Tanjungpura, 2022)
Cadmium Sulfide (CdS) is a photocatalyst material with a low energy band gap, which exhibits a potential application for the visible light spectrum. However, the serious photo-corrosion of CdS inhibits its wide applications. To prevent photo-corrosion, one can coat the CdS surface coated with an insulating material. The addition of this insulating layer will produce a barrier potential on the surface of the CdS thereby blocking the transmission of electrons and holes. If the thickness of this protective layer is thin enough the electron and hole can be transmitted by the quantum tunneling effect. Using a simple quantum mechanical model, the phenomena of electron and hole transmission through potential barriers due to the presence of a protective layer on the CdS surface can be analyzed. Based on this model, the effects of variations in thickness and type of protective layer on the performance of CdS photocatalyst materials are studied by calculating the transmission coefficient and injection efficiency values. The protective coatings used in this study were Aluminum Oxide (Al2O3), Hafnium Dioxide (HfO2), and Silicon Dioxide (SiO2). The results show that transmission decreases as the thickness of the protective increases. Among the three types of protective coatings used, HfO2 material has the potential to be used because it has the best injection efficiency value.